2018
DOI: 10.3390/molecules23040833
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid 8-O-Glucuronides from the Aerial Parts of Malva verticillata and Their Recovery Effects on Alloxan-Induced Pancreatic Islets in Zebrafish

Abstract: Malva verticillata (Cluster mallow), a leafy vegetable that has been popular in East Asia for a long time, has also been used in herbal teas and medicines. The aqueous fraction of the aerial parts of Malva verticillata, exhibiting a very high quantity of flavonoids compared to the EtOAc and n-BuOH fractions, exhibited significant recovery effects on pancreatic islets damaged by alloxan in zebrafish larvae. Thus, the bioactive components responsible for this anti-diabetic activity were investigated. A new flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 42 publications
0
43
0
1
Order By: Relevance
“…As shown in Table 1, LSE is mainly composed of Q3G and isoquercetin, which are considered to contribute to their biological properties in addition to quercetin and kaempferol. Previous studies have indicated that Q3G, a major antioxidative quercetin metabolite in human plasma, may exert antioxidant effects on alloxan-induced pancreatic islet damage in zebrafish [42]. Additionally, Q3G is reported to be as effective as quercetin in ameliorating insulin resistance by regulating the insulin receptor substrate 1 (IRS-1) function of the endothelium [43].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, LSE is mainly composed of Q3G and isoquercetin, which are considered to contribute to their biological properties in addition to quercetin and kaempferol. Previous studies have indicated that Q3G, a major antioxidative quercetin metabolite in human plasma, may exert antioxidant effects on alloxan-induced pancreatic islet damage in zebrafish [42]. Additionally, Q3G is reported to be as effective as quercetin in ameliorating insulin resistance by regulating the insulin receptor substrate 1 (IRS-1) function of the endothelium [43].…”
Section: Discussionmentioning
confidence: 99%
“…Each of the solvent Frs-EtOAc, n-BuOH, and aqueous-and compounds 1-4 were evaluated for their recovery effects against alloxan-induced PI damage in zebrafish larvae. Alloxan, a well known diabetogenic chemical, is reported to decrease β-cell mass in PIs [3]. Alloxan treatment significantly decreased PI size by 44.3% (p<0.0001) compared to the normal group (Figures 2 A, B, D, and E).…”
mentioning
confidence: 91%
“…Diabetes mellitus is one of the leading causes of mortality and disability worldwide and their relationship with pancreatic -cell in both patients and animal models was well known in several literatures [1][2][3]. Allopathic drugs for diabetes mellitus are limited due to a variety of side effects [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations